STRATEGI DAKWAH DALAM PENGEMBANGAN DAN PEMBERDAYAAN MASYARAKAT - Salmadanis Salmadanis (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2015)
The strategy is a method of propaganda tactics , tactics or maneuvers used in missionary activity . Propaganda strategy used in the propaganda effort with respect to some things like azaz philosophical , psychological and sociological . In religious societies , between the conception of psychology , sociology and religiosity should not be strictly separated , because if the case would lead to the conclusion that fatal . In sunatullah society will continue to evolve with the advances in modern science and technology . The problems faced by humans increasingly complex , the implications of advances in science and technology impact on various aspects of life such as religious , social , cultural, economic , political and so on